The design & management of a professional strength & conditioning training facility - Kurfurst, J. (Journal of Australian Strength and Conditioning, 2016)
Designing a new strength and conditioning (S&C) facility takes time, space, equipment and is often a major concern for S&C professionals. More often than not the S&C professional may have to develop a facility with a limited budget or resources and may be unaware of certain standards that need to be achieved to obtain accreditation. This article outlines recommendations regarding equipment choices, common dangers and problems associated with equipment and uses specific examples of the types of resources and equipment used at various strength and conditioning complexes both in Australia and the US.